Organ-Specific Surveillance and Long-Term Residency Strategies Adapted by Tissue-Resident Memory CD8+ T Cells - Stein, Jens V.; Ruef, Nora; Wissmann, Stefanie (Frontiers in Immunology, 2021)
Tissue-resident CD8+ T cells (CD8+ TRM) populate lymphoid and non-lymphoid tissues after infections as first line of defense against re-emerging pathogens. To achieve host protection, CD8+ TRM have developed surveillance strategies that combine dynamic interrogation of pMHC complexes on local stromal and hematopoietic cells with long-term residency. Factors mediating CD8+ TRM residency include CD69, a surface receptor opposing the egress-promoting S1P1, CD49a, a collagen-binding integrin, and CD103, which binds E-cadherin on epithelial cells. Moreover, the topography of the tissues of residency may influence TRM retention and surveillance strategies. Here, we provide a brief summary of these factors to examine how CD8+ TRM reconcile constant migratory behavior with their long-term commitment to local microenvironments, with a focus on epithelial barrier organs and exocrine glands with mixed connective – epithelial tissue composition.